(untitled) (Architecture Image Studies, 2025)
Islamic insurance, or Takaful, offers Shariah-compliant coverage based on shared responsibility, solidarity, and mutual support, rather than profit. In Somalia, interest in Takaful has grown, leading to the establishment of new institutions. However, limited research exists on the factors influencing individuals’ intention to adopt Takaful. This study investigates the impact of attitude, subjective norm, perceived behavioral control, awareness, and knowledge on adoption intention, using the Theory of Planned Behavior (TPB) as a framework. A total of 400 self-administered questionnaires were distributed across seven major cities in Somalia. Data were analyzed using SPSS, employing descriptive statistics, multiple regression, and tests of validity and reliability. The findings revealed that all examined variables positively influenced individuals’ intention to adopt Takaful. Despite general awareness, the study recommends that Takaful operators enhance promotional and educational efforts to improve public understanding and trust. Additionally, the integration of awareness and knowledge into the TPB model offers a broader perspective on Takaful adoption behavior in Somalia.